The Simplicity Argument and the Unconscious: Plotinus, Cudworth, Leibniz, and Kant - Mijuskovic, Ben Lazare (Philosophy & theology, 2008)
I argue that Kant’s four Paralogistic conclusions concerning (a) substantiality; (b1) unity and (b2) immortality, in the famous “Achilles argument”; (c) personal identity; and (d) metaphysical idealism, in the first edition Critique of Pure Reason (1781), are all connected by being grounded in a common underlying rational principle, an a priori (universal and necessary) presupposition, namely, that both the mind and its essential attribute of thinking are immaterial and unextended, i.e., simple. Consequently, despite Kant’s predilection for architectonic divisions and separations, I show that in fact the simplicity assumption grounds all four Paralogisms and reinforces Kant’s corresponding commitments to the principles of continuity and coherence. Further, I maintain that Kant, under the influence of his earlier Leibnizian and subjective idealist leanings, continued to be guided in the first edition Critique, not only in the Paralogisms but also in certain sections of the Analytic, by emphasizing unconscious activities, which once more reinforced his commitments to a paradigm of the simplicity, unity, and identity of self-consciousness or apperception.